2022
DOI: 10.1111/apps.12401
|View full text |Cite
|
Sign up to set email alerts
|

Addressing new leadership challenges in a rapidly changing world

Abstract: Addressing new leadership challenges in a rapidly changing worldLeadership is one of the most popular practical and research topics in applied psychology. This is not surprising because leadership is key for successfully managing businesses and organisations, and it is the driving force for tackling grand societal challenges. Unfortunately, leadership can also be at the root of societal problems. Currently, we are experiencing a large scale of changes in business and society that make leadership more important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…More than just a trend, this "new normal" will have lasting and powerful effects on the future of Emotional Intelligence: Constraints and Possibilities in Leadership Practices DOI: http://dx.doi.org/10.5772/intechopen.109977 education and school leadership. Also, school leaders can use data to make a change that is impactful and sustainable [1,2,7].…”
Section: Leadership For Changementioning
confidence: 99%
See 4 more Smart Citations
“…More than just a trend, this "new normal" will have lasting and powerful effects on the future of Emotional Intelligence: Constraints and Possibilities in Leadership Practices DOI: http://dx.doi.org/10.5772/intechopen.109977 education and school leadership. Also, school leaders can use data to make a change that is impactful and sustainable [1,2,7].…”
Section: Leadership For Changementioning
confidence: 99%
“…Researchers concluded that effective leadership behavior and practices, which facilitate change in the work setting includes building trust with stakeholder and employing strategies to implement an organizational culture that reflects trust and honesty, which results in a sense of belonging. Such strategies reinforce a commitment to organizational change [7,15,17,39].…”
Section: Leadership For Changementioning
confidence: 99%
See 3 more Smart Citations